Great Depression and the Rise of Female Employment: A New Hypothesis - Andriana Bellou; Emanuela Cardia (Institute of Labor Economics (IZA), 2018)
The cohorts of women born at the turn of the 20th century increased markedly their participation in the labor market when older. These are the first cohorts who worked after their childbearing years. In this paper, we document a link between their work behavior and the Great Depression. We show that the 1929 Crash attracted young women 15 to 34 years old in 1930 (whom we name D-cohort) into the labor market, possibly via an added-worker effect. Using several years of Census micro data, we further document that the same cohort remained or re-entered the labor market in the 1940s and 1950s and that its entire life cycle labor supply is tightly linked to the conditions dating back to the Great Depression. We argue that these facts are consistent with the hypothesis of a labor supply shift for this cohort triggered by the 1929 Crash.
Keywords: J21; N32; J01; 330; Great Depression; added worker effect; female labor supply